A new Middle Palaeolithic chert quarry and workshop site in Kalkashvand (Harsin, Kermanshah), Iran - Ghasiran, Sirvan Mohammadi; Mansouri, Sa’id; Beik Mohammadi, Khalilollah; Ghaffari Heris, Reza (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
Investigations carried out in the last century on the early settlements in various intermontane plains of Kermanshah in Central Zagros have produced abundant information and evidence on different phases of the Palaeolithic period. Most of the recorded caves, rock shelters, and open-air sites contain remains from the Middle Palaeolithic through the Epipalaeolithic times. The Harsin County is in the east Kermanshah Province in West Iran. The region allured human groups in different periods with its desirable climatic and environmental settings, such as freshwater sources, perennial rivers, rich vegetation and fertile soil, not to mention chert formations. Braidwood, Mortensen and Smith carried out the first systematic archaeological work in the region. In their 2002 survey, Motarjemand Mohammadifar recorded 125 sites dating to different periods, and the reappraisal of the regional investigations in 2008 added 68 additional sites to their list, of which 17 are of Middle or Upper Palaeolithic date.